2020
DOI: 10.1128/jvi.00451-20
|View full text |Cite
|
Sign up to set email alerts
|

Genetically and Antigenically Divergent Influenza A(H9N2) Viruses Exhibit Differential Replication and Transmission Phenotypes in Mammalian Models

Abstract: Low pathogenicity avian influenza A(H9N2) viruses, enzootic in poultry populations in Asia, are associated with fewer confirmed human infections but higher rates of seropositivity compared to A(H5) or A(H7) subtype viruses. Co-circulation of A(H5) and A(H7) viruses leads to the generation of reassortant viruses bearing A(H9N2) internal genes with markers of mammalian adaptation, warranting continued surveillance in both avian and human populations. Here, we describe active surveillance efforts in live poultry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…Ghana [14]. The human strain A/Hong Kong/1073/99 used in kinetics replication as control was also characterized in ferrets and did not show any increased virulence or airborne transmission ability [30]. These results suggest a similar zoonotic potential of Sub-Saharan…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Ghana [14]. The human strain A/Hong Kong/1073/99 used in kinetics replication as control was also characterized in ferrets and did not show any increased virulence or airborne transmission ability [30]. These results suggest a similar zoonotic potential of Sub-Saharan…”
Section: Discussionmentioning
confidence: 89%
“…At least 59 human cases of H9N2 have been reported in the world [2]. In Africa, ferrets [12,14,30]. Algerian viruses did not show any increase of virulence or airborne transmission ability in ferrets [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gross and microscopic pathology for the dead bird included congestion and haemorrhages of the lungs and ovarian follicles with oedema and mononuclear cell infiltration, hypertrophy of the liver with necrosis and mononuclear cell infiltration, and spleen atrophy with necrosis and lymphocyte infiltration. Belser et al (2020) reported the detection of 163 A(H9N2) positive oropharyngeal swabs and environmental (feces and water) samples collected between September 2018 and September 2019 in live poultry markets in Vietnam. 55 complete genome sequences were obtained: all clustered with Y280/G9 lineage A(H9N2) viruses and were grouped in two large sublineages named A and B in this study, and respectivrly related to candidate vaccine viruses A/chicken/Hong Kong/G9/1997 and A/Hong Kong/308/2014 or A/Anhui-Lujiang/39/2018.…”
Section: Detectionmentioning
confidence: 99%